Hubungan penggunaan smartphone dan kinerja akademik di kalangan mahasiswa - Morissan, Morissan (Jurnal Studi Komunikasi, 2020)
This research examined the relationship between smartphone usage and academic achievement in university students. The sample of this research was 598 university students in Jakarta. Several important factors, such as self-efficacy, academic efficacy, gender, smoking habit, and romantic relationships were taken into consideration in determining the relationship. First, and independent sample t-test and ANOVA were conducted to determine if academic performance was influenced by the three predictors (sex, smoking habit, and romantic relationship). Second, hierarchical multiple regression was done to find out whether there was a significant relationship between smartphone usage and academic performance by controlling the overall predictor variables. The findings revealed that the female group exhibited better academic performance, as did the students who did not smoke and had no romantic partners. Furthermore, the multiple hierarchical regression indicated that among all predictors examined, smoking habit was the most significant moderator that influences academic performance (Î² = -0.22, p